Exome analysis of a family with Wolff-Parkinson-White syndrome identifies a novel disease locus. - Bowles, Neil E; Jou, Chuanchau J; Arrington, Cammon B; Kennedy, Brett J; Earl, Aubree; Matsunami, Norisada; Meyers, Lindsay L; Etheridge, Susan P; Saarel, Elizabeth V; Bleyl, Steven B; Yost, H Joseph; Yandell, Mark; et al. (Am J Med Genet A, 2015)
Wolff-Parkinson-White (WPW) syndrome is a common cause of supraventricular tachycardia that carries a risk of sudden cardiac death. To date, mutations in only one gene, PRKAG2, which encodes the 5'-AMP-activated protein kinase subunit γ-2, have been identified as causative for WPW. DNA samples from five members of a family with WPW were analyzed by exome sequencing. We applied recently designed prioritization strategies (VAAST/pedigree VAAST) coupled with an ontology-based algorithm (Phevor) that reduced the number of potentially damaging variants to 10: a variant in KCNE2 previously associated with Long QT syndrome was also identified. Of these 11 variants, only MYH6 p.E1885K segregated with the WPW phenotype in all affected individuals and was absent in 10 unaffected family members. This variant was predicted to be damaging by in silico methods and is not present in the 1,000 genome and NHLBI exome sequencing project databases. Screening of a replication cohort of 47 unrelated WPW patients did not identify other likely causative variants in PRKAG2 or MYH6. MYH6 variants have been identified in patients with atrial septal defects, cardiomyopathies, and sick sinus syndrome. Our data highlight the pleiotropic nature of phenotypes associated with defects in this gene.
Keywords: Adult; AMP-Activated Protein Kinases; Cardiac Myosins; Exome; Female; Genetic Loci; Humans; Male; Myosin Heavy Chains; Pedigree; Potassium Channels, Voltage-Gated; Wolff-Parkinson-White Syndrome